74 Seaside Avenue [compact disc, unabridged] - Macomber, Debbie (Macomber, Debbie. Cedar Cove series., 2007)
Meet blissfully happy newlyweds Bobby and Teri Polger. He's an international chess champion, she's a salon stylist, and both will soon be confronted by deadly threats from a vindictive Russian rival.